Réponses

2013-12-18T18:28:09+01:00
A=(2x+1)(x-5) 
1) Développer et réduire A
A=(2x+1)(x-5) 
=2x²-10x+x-5
=2x²-9x-5

2) Calculer A pour x= -3
2x²-9x-5
=2*(-3)²-9*(-3)-5
=2*9-27-5
=18-27-5
=-9-5
=-14

3) Résoudre l'équation A=0   
A=(2x+1)(x-5)=0
2x+1=0                        ou x-5=0
2x=1                                 x=5
x=1/2

donc x=1/2 ou x=5 pour que l'équation soit égale à 0
2013-12-18T18:30:30+01:00
1) A=(2x+1)(x-5)
A= (2x*x)+(2x*(-5))+(1*x)+(1*(-5))
A=2x^2+(-10x)+x+(-5)
A:2x^2-10x+x-5
A=2c^2-9x-5

2) A=(2*(-3)+1)(-3-5)
A=(-6+1)(-3-5)
A=(-6*(-2))+(-6*(-5))+(1*(-3))+(1*(-5))
A=12+30+(-3)+(-5)
A=12+30-3-5
A=34